Peningkatan Literasi Pengelolaan Keuangan Melalui Event BERANDA X OJK 2023 - Nabiilah Rizky Auliya; Imam Syafganti; Muhammad Iqbal Katik Rajoendah; Annisa Wardhani; Yuningsih Yuningsih (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
Financial literacy is a fundamental necessity that everyone should possess to avoid financial issues. The Financial Services Authority (Otoritas Jasa Keuangan) is endeavoring to expand its financial literacy campaign program aimed at educating and enhancing the financial literacy of the community, with the current primary target being Housewives. Efforts supporting the Financial Services Authority's program to achieve this goal include socialization through the organization of the talk show event